Political Budget Cycles: Evidence from Swiss Cantons - Guido Baldi; Stephan Forster (ZBW – Leibniz Information Centre for Economics, 2019)
Models of political budget cycles assume that politicians use fiscal policy to increase their chances of re-election. However, empirical results for advanced economies provide ambiguous support for the existence of such electoral cycles. Also, studies focusing on the regional or local level of advanced economies have found a variety of different results. In this paper, we use data at the sub-federal level of Switzerland from 1978 through 2015 to test for the presence of political budget cycles. Swiss regions called cantons are highly autonomous with regard to budgetary policy and have established direct democratic systems with frequent referendums that often affect budgetary issues. In most cantons, there are fiscal policy rules that restrict the budgetary leeway of governments. Overall, the system of government is designed to foster consensus seeking and gradual adjustment. These features should make the short-run opportunistic or partisan use of fiscal policy less likely in Swiss cantons. Rather surprisingly, however, we find at least some evidence for an electoral cycle in government spending. For government revenue or the overall budget, our empirical results do not point to an electoral cycle.
Keywords: D72; E62; H62; 330; Political budget cycle; fiscal policy; direct democracy